Perspectives on Populus spp. (Salicaceae) bud extracts as antioxidant and anti-inflammatory agents. Issue 6 (19th March 2022) - Pannucci, Elisa; D'Eliseo, Donatella; Ieri, Francesca; Romani, Annalisa; Santi, Luca; Bernini, Roberta; Sabatti, Maurizio; Velotti, Francesca
Abstract: Hydroalcoholic extracts obtained from buds of P. nigra, P. deltoides and P. trichocarpa were characterized by HPLC-DAD-MS analysis and subsequently evaluated in vitro for their antioxidant and anti-inflammatory activities. ABTS and DPPH assays evidenced that P. nigra showed the best antioxidant activity in line with its highest total phenolic content. The analysis of the anti-inflammatory activity clearly demonstrated that all extracts suppressed the production of key pro-inflammatory cytokines (IL-6, Il-1β and TNF-α) and HMGB1 inflammatory danger signal. These results show antioxidant and critical anti-inflammatory activities mediated by the extracts, emphasising their potentiality as therapeutic agents. GRAPHICAL ABSTRACT: